An investigaton of the innate immune response to the vaccine adjuvant chitosan - Carroll, Elizabeth (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2015)
Vaccination is widely regarded as one of the most successful medical intervention strategies to have been introduced. Despite its resounding success, significant challenges in the field of vaccine research still remain. Suboptimal and reactogenic vaccines currently in use must be replaced by safer and more effective alternatives. Furthermore, there are a number of diseases for which the development of efficacious vaccines has proved difficult; this is particularly true for diseases which require cellular immune responses to confer protection. One of the reasons for this is the lack of vaccine adjuvants currently available that can promote cellular immunity.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin